A modelling of influenza a (H1N1) with vaccination - Hiew Suhua, 1991- author; Fuaada Mohd Siam, supervisor; Fakulti Sains (2015)
Project Paper (Sarjana Muda Sains serta Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2015